Fingering convection in accreting hydrogen white dwarf - Wachlin, Felipe Carlos (2019)
The accretion of heavy material from debris disk on the surface of hydrogen-rich white dwarfs induces a double diffusivity instability known as the fingering convection. It leads to an efficient extra mixing which brings the accreted material deeper in the star than by considering only mixing in the surface dynamical convection zone, in a time scale much shorter than that of gravitational settling. We performed numerical simulations of a continuous accretion of heavy material having a bulk Earth composition on the two well studied DAZ and ZZ Ceti pulsators GD 133 and G 29-38. We find that the existence of fingering convection implies much larger accretion rates to explain the observed abundances than previous estimates based on the standard mixing length theory and gravitational settling only.